Decent Work and the Digital Gig Economy : A Developing Country Perspective on Employment Impacts and Standards in Online Outsourcing, Crowdwork, etc. /: A Developing Country Perspective on Employment Impacts and Standards in Online Outsourcing, Crowdwork, etc. (2017) - Heeks, Richard, 1960-
No abstract available